2022
DOI: 10.1108/ajar-06-2021-0097
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of corporate announcements on stock returns during the global pandemic: evidence from the Indian stock market

Abstract: PurposeThe authors examine the impacts of corporate announcements on stock returns during the pandemic stress.Design/methodology/approachThe authors employ the event study methodology with the market model on a sample of 90 events (announcement and ex-date).FindingsThe authors find that all the corporate announcements do not impact the stock returns in a similar pattern. While the bonus announcement, ex-bonus and ex-split events led to positive significant abnormal returns on the event date, the rights issue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
0
10
1
1
Order By: Relevance
“…Prakash & L (2022) examined the reaction of stock to dividends announced during the pre-and postpandemic period and found that the market reaction around the dividend announcement was positive and significant compared to an early period. In another, study, Pandey et al, (2022) observed that only specific events, namely bonus announcement, ex-bonus and ex-split, led to positive and significant impact whereas, the market did not react to the announcement of the right issue and stock split. The study further observed that even positive events during a pandemic result in negative market reactions.…”
Section: Review Of Literaturementioning
confidence: 93%
See 2 more Smart Citations
“…Prakash & L (2022) examined the reaction of stock to dividends announced during the pre-and postpandemic period and found that the market reaction around the dividend announcement was positive and significant compared to an early period. In another, study, Pandey et al, (2022) observed that only specific events, namely bonus announcement, ex-bonus and ex-split, led to positive and significant impact whereas, the market did not react to the announcement of the right issue and stock split. The study further observed that even positive events during a pandemic result in negative market reactions.…”
Section: Review Of Literaturementioning
confidence: 93%
“…Corporate actions, namely dividends, bonuses, rights and stock-split announcements, are motivated towards influencing stock prices and have a significant impact on stock returns (Pandey et al, 2022). However, the extent of the impact varies significantly based on the timing of announcements, types of announcements and place of announcements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini karena terdapat asimetri informasi antara pihak perusahaan dengan pihak luar. Untuk mengurangi terjadinya asimetri informasi tersebut, maka perusahaan memberi sinyal kepada pihak luar, salah satunya seperti laporan keuangan tahunan (Pandey et al, 2022).…”
Section: Pendahuluanunclassified
“…The reaction can be a positive reaction or a negative reaction. These positive reactions and negative reactions can be used as a basis to find out whether this supports the dividend signaling theory (Pandey et al, 2022).…”
Section: Introductionmentioning
confidence: 95%